2020
DOI: 10.1089/bfm.2020.0175
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole During Pregnancy and Lactation: Esomeprazole Levels in Maternal Serum, Cord Blood, Breast Milk, and the Infant's Serum

Abstract: Background: Esomeprazole is the S-isomer of omeprazole and is used to treat stomach acid-related diseases. Most data regarding the safety of esomeprazole during pregnancy are derived from studies on omeprazole, and the data characterizing esomeprazole transfer across the placenta and excretion into breast milk are limited. In this report, we discuss the safety of esomeprazole with reference to drug concentrations in maternal and neonatal blood and breast milk. Materials and Methods: After the patient provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Specifically, these studies have not shown any increased risk for congenital abnormalities, spontaneous miscarriage, or preterm delivery. [17][18][19] Thus, esomeprazole is likely to be safe in pregnancy. In this study we further reduced the chance of such risks by using the drug for a relatively short period in the late second and early third trimesters, well past the time of organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these studies have not shown any increased risk for congenital abnormalities, spontaneous miscarriage, or preterm delivery. [17][18][19] Thus, esomeprazole is likely to be safe in pregnancy. In this study we further reduced the chance of such risks by using the drug for a relatively short period in the late second and early third trimesters, well past the time of organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Spectrophotometric methods are the most common [1.2.3.5.6]. liquid chromatography [7]. RP_HPlC using diclofenac sodium and mass chromatography supercritical liquid chromatography HPLC using oxytetracycline, tindazole and micro-extraction liquid chromatography [2].…”
Section: Introductionmentioning
confidence: 99%
“…Є дані щодо безпеки від дуже великих когорт, які прийшли до висновку про відсутність для ІПП тератогенного ризику навіть після впливу у І триместрі [68]. Мета-аналіз повідомив про зв'язок між пренатальним впливом та дитячою астмою, але незрозуміло, чи є цей зв'язок причинним фактором або чи можуть певні асоціативні змінні пояснити цей висновок [41].…”
unclassified